2016
DOI: 10.1093/nar/gkw922
|View full text |Cite
|
Sign up to set email alerts
|

The multifaceted influence of histone deacetylases on DNA damage signalling and DNA repair

Abstract: Histone/protein deacetylases play multiple roles in regulating gene expression and protein activation and stability. Their deregulation during cancer initiation and progression cause resistance to therapy. Here, we review the role of histone deacetylases (HDACs) and the NAD+ dependent sirtuins (SIRTs) in the DNA damage response (DDR). These lysine deacetylases contribute to DNA repair by base excision repair (BER), nucleotide excision repair (NER), mismatch repair (MMR), non-homologous end joining (NHEJ), homo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
100
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 86 publications
(103 citation statements)
references
References 190 publications
(312 reference statements)
2
100
0
1
Order By: Relevance
“…So far, information concerning the interplay between oxidative stress and ER stress in the specific context of seed germination is missing. However, based on these findings, we cannot and sensitizing cells to genotoxic agents (Roos & Krumm, 2016). In Pagano et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…So far, information concerning the interplay between oxidative stress and ER stress in the specific context of seed germination is missing. However, based on these findings, we cannot and sensitizing cells to genotoxic agents (Roos & Krumm, 2016). In Pagano et al, 2017).…”
Section: Discussionmentioning
confidence: 92%
“…truncatula seeds at the radicle protrusion stage (Figure a). In animal cells, HDAC inhibitors play contrasting roles in DDR, by promoting DNA repair through chromating relaxation, suppressing the catalytic activity of specific repair complexes, and sensitizing cells to genotoxic agents (Roos & Krumm, ). In our system, comet assay provided evidence of DNA damage accumulation in NaB‐treated seeds at the radicle protrusion stage, in agreement with Pagano et al () who reported genotoxic damage in M .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that HDACI can inhibit the catalytic activity of HDAC, change the chromosome structure, activate the gene transcription, correct the chromosomes from "closed" to "open" state, play a neuroprotective role, including: inhibition of neuronal apoptosis, regulation of microglia/macrophage polarization, reduction of inflammatory response, promotion of nerve regeneration 5,20 . 21,22 . Our results also confirm that HDACI has a protective effect in cerebral ischemia reperfusion, which may be associated with activation of Akt/GSK-3β pathway.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Evidence in different organisms strongly suggests that nuclear sirtuins are particularly relevant in the signaling pathways that repair DSBs: non-homologous end joining (NHEJ) and homologous recombination (HR) 19 (Fig. 2).…”
Section: Sirtuins and Double-strand Break Repair: What We Learn From mentioning
confidence: 99%